Los pobres como agentes de su desarrollo, la lucha contra la pobreza y la exclusión desde lo local - Luis Portales (Revue Interventions Économiques)
In 2010, one out of five human beings is living in poverty. These poverty conditions are exacerbated in rural areas, which concentrate 70 % of population in extreme poverty globally. One of the main causes of this form of poverty is the socio-economic exclusion in which these people live. Local development aims to address this issue of extreme exclusion. Its premise is that local actors are responsible to generate social inclusion strategies that allow the poor to leave this condition. This article presents the experience of the implementation of this intervention-action model in a Mexican rural community. The results of the implementation were the reduction of exclusion patterns and the construction of the necessary foundations to continue to carry out actions that contribute to local development and long-term poverty reduction.